Developing Games for Young Learners to Learn English Using Adobe Flash Cs3 - MV. Joyce Merawati BRR.; Achmad Faisal Aini (Magister Scientiae, 2011)
Children like to play games with computers. This stimulates teachers and parents to make use of computers to enhance the children’s learning. However, most of the available games are not in line with the school curriculum. Creative teachers usually like to develop suitable teaching materials for their learners. Through this paperwe would share our experience when developing a vocabulary game for elementary school learners although our knowledge about computer programs is limited. This paper talks about the process of developing the game starting from some considerations when preparing and deciding the game, selecting topic, words, until writing short texts so that they are line with the English curriculum of primary schools in Indonesia. Some technical processes using Adobe Flash CS3 are discussed briefly to make it user friendly for young learners. Finally, the pedagogical aspects of the game, the problems encountered and the solution are explained